Answer:
g(f(x)) = -6x+6.
Step-by-step explanation:
It is given that,
f(x) = -3x + 2 and g(x) = 2x – 5
We need to find g(f(x)).
Put it into g(x).
g(f(x)) = 2(-3x + 2)+2
= -6x+4+2
=-6x+6
Hence, the value of g(f(x)) is -6x+6.
Answer:
6
Step-by-step explanation:
If p equals 15 then plug 15 in for p and take 15-9=6. pretty sure that's what they are looking for there.
Answer:
Step-by-step explanation:
A person invested $2,500 in an account growing at a rate allowing the money to double every 11 years. How long, to the nearest tenth of a year would it take for the
value of the account to reach $3,800?
The formula for exponential growth given as:
A(t) = Ao (1/2)^t/t½
A(t) = Amount after time t = $3,800
Ao = Initial amount invested = $2500
t = Time in years
t½ = Time it takes to double = 11 years
Hence,
3800 = 2500(1/2)^t/11
Divide both sides by 2500
3800/2500 = 2500(1/2)^t/11/2500